The degree of use of the Artificial Intelligence Application (ChatGPT) by Arab Open University students in psychological counselling - Al-Shuaili, Moosa Sulaiman; Al-Riyami, Elham AbdulRahman (Journal of Educational and Psychological Sciences, 2025)
This research aims to study the degree of use of the artificial intelligence application (ChatGPT) by Arab Open University students in psychological counselling. The researchers used the descriptive-analytical method, where the sample consisted of 208 male and female students from AOU. To collect data, the researchers used a questionnaire, and to analyze it, they used the arithmetic means, standard deviations and two-tailed tests. The study concluded with the following results: The degree of use of Chat GPT by AOU students was high, ranging between 4.18 and 2.89; the degree of their use of the same program in student counselling was moderate, ranging between 3.80 and 2.85. There are no statistically significant differences attributable to the variables of gender and age in the degree of use of ChatGPT among AOU students.
Keywords: ChatGPT; Arab Open University; psychological counselling